Deployment of Genetic and Genomic Tools Toward Gaining a Better Understanding of Rice-Xanthomonasoryzae pv. oryzae Interactions for Development of Durable Bacterial Blight Resistant Rice - Kumar, Anirudh; Kumar, Rakesh; Sengupta, Debashree; Das, Subha Narayan; Pandey, Manish K.; Bohra, Abhishek; Sharma, Naveen K.; Sinha, Pragya; Sk, Hajira; Ghazi, Irfan Ahmad; Laha, Gouri Sankar; Sundaram, Raman Meenakshi (Frontiers in Plant Science, 2020)
Rice is the most important food crop worldwide and sustainable rice production is important for ensuring global food security. Biotic stresses limit rice production significantly and among them, bacterial blight (BB) disease caused by Xanthomonas oryzae pv. oryzae (Xoo) is very important. BB reduces rice yields severely in the highly productive irrigated and rainfed lowland ecosystems and in recent years; the disease is spreading fast to other rice growing ecosystems as well. Being a vascular pathogen, Xoo interferes with a range of physiological and biochemical exchange processes in rice. The response of rice to Xoo involves specific interactions between resistance (R) genes of rice and avirulence (Avr) genes of Xoo, covering most of the resistance genes except the recessive ones. The genetic basis of resistance to BB in rice has been studied intensively, and at least 44 genes conferring resistance to BB have been identified, and many resistant rice cultivars and hybrids have been developed and released worldwide. However, the existence and emergence of new virulent isolates of Xoo in the realm of a rapidly changing climate necessitates identification of novel broad-spectrum resistance genes and intensification of gene-deployment strategies. This review discusses about the origin and occurrence of BB in rice, interactions between Xoo and rice, the important roles of resistance genes in plant’s defense response, the contribution of rice resistance genes toward development of disease resistance varieties, identification and characterization of novel, and broad-spectrum BB resistance genes from wild species of Oryza and also presents a perspective on potential strategies to achieve the goal of sustainable disease management.